Business Creation through Creativity and Innovation among Students - Suryani, Ni Kadek; Dewi, Luh Komang Candra; Foeh, John EHJ (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2021)
This study investigates the relationship between creativity, innovation, and the feasibility of business ideas created by students while taking entrepreneurship courses. Data were collected using an online questionnaire. Hypothesis testing uses structural equation modeling. The test results show that creativity has no direct effect on the feasibility of a business idea. Creativity affects the feasibility of a business idea through innovation. Creativity has a positive impact on innovation, and innovation positively impacts the feasibility of a business idea. This research proves creativity itself is not enough to produce a viable business; it requires innovation.